Radiation Yield and Radicals Produced in Irradiated Poly (Butylene Succinate) - Meri Suhartini; Fumio Yoshii; Naotsugu Nagasawa; Hiroshi Mitomo (Atom Indonesia, 2004)
The main chemical effects of ionizing irradiation on polymers are crosslinking and chain scission. Both processes occur simultaneously and their yields determine the final results of processing. The radiation yield of crosslinking could be determined by several methods depending on the characteristics of the material and properties of the gel. Radiation parameters of gelation, such as gelation dose and ratio of scission yield to crosslinking yield, as well as their values were estimated. In this study, those parameters depend on the amount of Trimethallyl isocyanurate (TMAIC) in Poly(butylene succinate) (PBS), molecular weight of PBS, and irradiation condition. In the absence of TMAIC, higher molecular weight of PBS required less energy to start gelation process compare to lower molecular weight of PBS. While in the presence of TMAIC all of the PBS samples require similar energy to start gelation process. The existence of macroradicals were observed by Electron Spin Resonance measurements. The result showed that the spectra consisted of signals derived from radicals on carbon nearby carbonyl, and signals derived from radicals on carbon reside between two similar carbon on polymer, both of radicals lead to crosslinking.